New literacies : critical reading, writing, and viewing : English workbook - Cequeña, Maria; Pulido, Dennis; Tan, Neslie (Laguna : Trailblazer Publications Asia, Inc., 2013)
"This book is the first workbook covers multi-literacies such as academic literacy, media literacy, information literacy, and social/cultural literacy. These are critical skills in the 21st century that is saturated by media and bombarded by information. Its worktext will help you to cope with the demands of academic life as reading texts become more complex and writing assignments more challenging. Your writing fears will be addressed as this book leads you by the hand in the step-by-step composing process and in following the academic writing style that you may not be familiar with. Each lesson provides reading, writing, viewing and language exercises in context wherein, these will be your stepping stones when you do the writing assignments".
Includes references.
English text.
Keywords: Academic writing--Handbooks, manuals, etc; English language--Rhetoric.; English language--Composition and exercises